The tempest - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. Works 2008., 2008)
"This book presents a historical overview of The Tempest in performance, recommends film versions, takes a detailed look at specific productions and includes interviews with three leading directors - Peter Brook, Sam Mendes and Rupert Goold - so that we may get a sense of the extraordinary variety of interpretations that are possible, a variety that gives Shakespeare his unique capacity to be reinvented and made 'our contemporary' four centuries after his death."--Jacket.